PROFIL EFIKASI DAN KEMANDIRIAN BELAJAR MAHASISWA BERPRESTASI UNIVERSITAS RIAU - Rahmita Budiartiningsih; Evi Suryawati; Syarifah Nur Siregar; Geovani Meiwandad; Zaldi Zaldi (Pusat Studi GESI - UWP, 2023)
This study aims to determine the profile of Self-Efficacy (SE) and Self-Directed Learning (SDL) of students who excel academically and non-academicly based on gender at the University of Riau. The study is expected to provide an overview of the potential for academic and non-academic achievements and the correlation of these achievements to the success of students in completing studies, getting jobs, entrepreneurship and continuing their studies. The instrument used is a questionnaire using a Likert scale. The SE indicator consists of 5 indicators, namely (confidence in completing tasks, self-motivation, hard work, overcoming obstacles, and completing tasks in a broad or narrow perspective) The SDL indicator consists of 5 indicators, namely (awareness), learning strategies, activities learning activities, evaluations, and interpersonal skills. Data analysis was carried out descriptively to map the profiles of academic and non-academic achievement students related to SE and SDL. The results showed that the number of male outstanding students was 31% 69% female, SE male 4.36 female 4.31, male SDL 4.20 female 4.18, male students have academic and non-academic achievements of 60% female 56%. This shows there is no the real difference between SE and SDL in male and female students, they have the same opportunities to achieve academic and non-academic achievements.Keywords: self-efficacy, learning independence, achievement, gender